In Vitro Trueness and Precision of Intraoral Scanners in a Four-Implant Complete-Arch Model - Dimitrios Spagopoulos; George Kaisarlis; Foteini Spagopoulou; Demetrios J. Halazonetis; Jan-Frederik Güth; Efstratios Papazoglou (MDPI AG, 2023)
(1) Background: New intraoral (IOS) and laboratory scanners appear in the market and their trueness and precision have not been compared. (2) Methods: Seven IOS and two laboratory scanners were used to scan a mandibular edentulous model with four parallel internal hexagon implant analogues and PEEK scan bodies. Digital models in Standard Tessellation Language (STL) were created. The master model with the scan bodies was scanned (×10) with a computerized numerical control 3D Coordinate Measuring Machine (CMM). The short (distances of adjacent scan posts) and long distances (distances of the scan posts with non-adjacent sites in the arch) among the centroids of the four analogues were calculated using CMM special software. Trueness (comparisons with the master model) and precision (intragroup comparisons) were statistically compared with ANOVA, chi-square and Tukey tests. (3) Results: Laboratory scanners had the best trueness and precision compared to all IOSs for long distances. Only iTero (Align Technologies Inc., Milpitas, CA, USA) had comparable trueness with one laboratory scanner in short and long distances. For short distances, CS3600 (Carestream Health, Inc., Rochester, NY, USA), Omnicam, Primescan (Sirona Dental Sys-tems GmbH, Bens-heim, Germany) and TRIOS 4 (3Shape A/S, Copen-hagen, Denmark) had similar trueness to one laboratory scanner. From those, only Omnicam and Primescan had similar precision as the same laboratory scanner. Most IOSs seem to work better for smaller distances and are less precise in cross-arch distances. (4) Conclusions: The laboratory scanners showed significantly higher trueness and precision than all IOSs tested for the long-distance group; for the short distance, some IOSs were not different in trueness and precision than the laboratory scanners.